The Short-term Stability of a Simulated Differential Astrometric Reference Frame in the Gaia Era. (31st March 2017) - Abbas, Ummi; Bucciarelli, Beatrice; Lattanzi, Mario G.; Crosta, Mariateresa; Gai, Mario; Smart, Richard; Sozzetti, Alessandro; Vecchiato, Alberto
Abstract: We use methods of differential astrometry to construct a small field inertial reference frame stable at the micro-arcsecond level. Such a high level of astrometric precision can be expected with the end-of-mission standard errors to be achieved with the Gaia space satellite using global astrometry. We harness Gaia measurements of field angles and look at the influence of the number of reference stars and the star's magnitude as well as astrometric systematics on the total error budget with the help of Gaia -like simulations around the Ecliptic Pole in a differential astrometric scenario. We find that the systematic errors are modeled and reliably estimated to the μ as level even in fields with a modest number of 37 stars with G  < 13 mag over a 0.24 square degrees field of view for short timescales of the order of a day with high-cadence observations such as those around the North Ecliptic Pole during the EPSL scanning mode of Gaia for a perfect instrument. The inclusion of the geometric instrument model over such short timescales accounting for large-scale calibrations requires fainter stars down to G  = 14 mag without diminishing the accuracy of the reference frame. We discuss several future perspectives of utilizing this methodology over different and longer timescales.